Tourist Perception of Tourism Service Satisfaction (Case Study: Pantai Kelapa Forest Tourism in Tuban) - Hendra Suwardana; Miftachul Munir; Muhammad Yusuf (INNOVATION RESEARCH JOURNAL, 2021)
Pantai Kelapa forest tourism is one of the marine tourism objects in Tuban Regency which is quite well known outside the region. Pantai Kelapa has several rides that are not in ferior when compared to other beaches on the coast of Tuban. The purpose of this study was to determine the characteristics of tourists, facilities, services, objects, accessibility, the development of tourist attractions in Pantai Kelapa based on tourist responses. The method used is descriptive qualitative, namely research that describes, summarizes various problems, then draws to the surface as a feature or description of certain conditions, situations or variables. Data collection techniques include dat a primary (observation, interview, documentation) and secondary data (study literature).techniques analysis covering data reduction (data reduction), display data presentation), (data conclusion drawing (inference). The results showed that the tourists 're sponses to the satisfaction of Pantai Kelapa tourism services, the satisfaction of Pantai Kelapa tourism services, were good. It was seen from the respondents' answers strongly agree with 51% and 54% agree on the variables questionnaire given. So from the responses given by respondents, it can be concluded that the quality of service to tourists is good. By doing this research, it is hoped that it can provide recommendations for the development of rides according to the needs of tourists to increase tourist attractiveness and maintain naturalness in the Pantai Kelapa tourism area so that tourist satisfaction with services in Pantai Kelapa tourism increases.